The antileukemic effects of saffron (Crocus sativus L.) and its related molecular targets: A mini review. Issue 4 (15th January 2019) - Moradzadeh, Maliheh; Kalani, Mohamad Reza; Avan, Amir
Abstract: Saffron ( Crocus sativus L.), and its main constituents, crocin, and crocetin have shown promising effects as an antileukemic agent in animal models and cell culture systems. Saffron retards the growth of cancer cells via inhibiting nucleic acid synthesis and enhancing antioxidative system. It can induce apoptosis and chemosensitivity via inhibiting multidrug resistance proteins. Saffron also induces differentiation pathways via inhibiting promyelocytic leukemia/retinoic acid receptor‐α, histone deacetylase1, and tyrosyl DNA phosphodiesterase‐1 as well. The present review highlights the most recent findings on the antileukemic effects of saffron and its underlying molecular targets. The emerging evidence suggests that saffron has a selective toxicity effect against leukemic cells while is safe for the normal cells.